North Atlantic Ice‐Rafting, Ocean and Atmospheric Circulation During the Holocene: Insights From Western Mediterranean Speleothems. Issue 13 (3rd July 2019) - Ait Brahim, Y.; Wassenburg, J. A.; Sha, L.; Cruz, F. W.; Deininger, M.; Sifeddine, A.; Bouchaou, L.; Spötl, Christoph; Edwards, R. L.; Cheng, H.
Abstract: In this study, we present a Holocene rainfall index based on three high‐resolution speleothem records from the Western Mediterranean, a region under the influence of the westerly winds belt modulated by the North Atlantic Oscillation (NAO). On centennial to millennial timescales, we show that the North Atlantic ice‐rafting events were likely associated with negative NAO‐like conditions during the Early Holocene and the Late Holocene. However, our data reveal that this is not clearly the case for the mid‐Holocene ice‐rafting events, during which we also show evidence of positive NAO‐like patterns from other paleo‐oceanographic and paleo‐atmospheric data. Hence, contradictory mechanisms involving prolonged periods of both north and south shifts of the westerly winds belt (resembling positive and negative NAO‐like patterns) might at least partially trigger or amplify the ice‐rafting events and the slowdown of the Atlantic Meridional Overturning Circulation. Plain Language Summary: During the Holocene, periods of enhanced ice‐rafting, associated with cooling and sea ice expansion in the North Atlantic high latitudes, have been recognized over distant regions. While the causes of these events are still a matter of debate, changes in the atmospheric circulation have been proposed as a potential trigger or amplifier. Here, we use speleothems to establish a precisely dated record of rainfall variability in the Western Mediterranean, a highly sensitive region to the westerly winds belt modulated by the North Atlantic Oscillation. Our results reveal new insights about the dynamics of NAO‐like patterns during the Holocene. On centennial to millennial timescales, prolonged periods of both north and south shifts of the westerly winds belt might trigger or amplify the slowdown of the Atlantic Meridional Overturning Circulation and the North Atlantic ice‐rafting. However, not all ice‐rafting events are associated with either positive or negative NAO‐like conditions. Key Points: A high‐resolution multi‐speleothem rainfall index describes the Holocene rainfall variability in the Western Mediterranean On centennial to millennial scales, negative NAO‐like conditions were likely associated with the Early and Late Holocene ice‐rafting events Different mechanisms involving north and south shifts of the westerly winds belt might contribute to ice‐rafting and the AMOC slowdown